2021
DOI: 10.3390/ma14133711
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Assisted Brittle Fracture Behavior of Low Alloy 30CrMo Steel Based on the Combination of Experimental and Numerical Analyses

Abstract: Compact-tension (CT) specimens made of low alloy 30CrMo steels were hydrogen-charged, and then subjected to the fracture toughness test. The experimental results revealed that the higher crack propagation and the lower crack growth resistance (CTOD-R curve) are significantly noticeable with increasing hydrogen embrittlement (HE) indexes. Moreover, the transition in the microstructural fracture mechanism from ductile (microvoid coalescence (MVC)) without hydrogen to a mixed quasi-cleavage (QC) fracture and QC +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…The rst area consists of solidi cation or hot cracks c) characterized by a dendritic structure, while the second area corresponds to cold cracks d) exhibiting transgranular and intergranular fracture surfaces. These observations provide clear indications of HAC, as previously demonstrated by [39,40].…”
Section: Fractographysupporting
confidence: 87%
“…The rst area consists of solidi cation or hot cracks c) characterized by a dendritic structure, while the second area corresponds to cold cracks d) exhibiting transgranular and intergranular fracture surfaces. These observations provide clear indications of HAC, as previously demonstrated by [39,40].…”
Section: Fractographysupporting
confidence: 87%
“…As is found in [ 41 ], Li et al conducted a series of experimental studies on 30CrMo steel, and the second conclusion is similar to their experimental results. Figure 14 is a schematic drawing of a finite element with cracks in 2-D coordinates.…”
Section: Numerical Experimentssupporting
confidence: 82%
“…In recent years, researchers have conducted extensive studies on the hydrogen embrittlement of 30CrMo steel. For instance, Li [8] performed fracture toughness testing on 30CrMo steel CT specimens after hydrogen charging and verified the experimental results using finite element analysis. The study found that with prolonged hydrogen charging, the CTOD-R curve exhibited a decreasing trend, resulting in an accelerated crack propagation rate and reduced crack propagation resistance.…”
Section: Introductionmentioning
confidence: 93%